Diet and Stress Patterns Linked to Blood Pressure in Young Adult Students: Pola Makan dan Stres yang Terkait dengan Tekanan Darah pada Mahasiswa Dewasa Muda - Jesyca Isabel Anggraini; Atik Sri Wulandari; Diana Tri Ratnasari; Puput Ayu Novitasari; Tri Anisa Istiqomah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Hypertension increasingly appears among young adults, with lifestyle factors often shaping variations in blood pressure. Specific background: Medical students frequently experience academic demands, irregular routines, and stress, making them a relevant group for examining dietary patterns and psychological conditions connected to blood pressure. Knowledge gap: Limited studies have assessed diet and stress simultaneously in a homogeneous young adult cohort with similar academic pressures. Aims: This study explored diet and stress patterns linked to blood pressure categories in medical students. Results: Among 81 respondents, most reported good dietary habits and normal blood pressure, while stress ranged from normal to very severe. Statistical analysis showed no measurable connection between diet patterns and blood pressure, whereas stress levels corresponded to differences across blood pressure categories. Novelty: The study focuses on a single academic cohort with shared workloads, offering a clearer understanding of how stress aligns with blood pressure variations. Implications: These findings highlight the need for structured stress-management strategies in academic environments to support cardiovascular health among young adult students. Highlights Diet patterns show no observable link to blood pressure among young adult students. Stress levels correspond to variations in blood pressure categories within the cohort. Academic environments may require targeted stress-management initiatives to support student well-being. Keywords Diet Pattern, Stress Level, Blood Pressure, Young Adult Students, Medical Education